Precise Hole Drilling in PMMA Using 1064 nm Diode Laser CNC Machine - Jinan A. Abdulnabi; Thaier A. Tawfiq; Anwaar A. Al-Dergazly; Ziad A. Taha; Khalil I. Hajim (Advances in Materials Science and Engineering)
This paper represents the outcome of efforts that intended to achieve laser hole drilling execution in polymethylmethacrylate (PMMA) of 2.5 mm thickness using 1064 nm diode laser of 5 W output power. Different laser beam powers, exposure time, and positions of the laser spot were taken into consideration with respect to the workpiece. The workpieces were tested in the existence of low-pressure assist gas (20–60 mmHg of air). The experimental results were supported by the predicted results of the analytical model.